Bamboozled - Rabe, Tish; Fordham, Denise Moroney, Christopher (Bantam London, 2011)
The Cat's taking Nick and Sally off to Bam-wam-a-boo-boo. If you're really quick, you can go, too! they need to find a present for Pammy, their dear panda friend. The gift they've chosen is light, hollow and can bend.--Cover